Travel in the Digital Age: How Social Media Drives Brand Image and Emotional Attachment - Mahato, Surendra; Sharma, Dilli Raj (Kshitiz Management Review, 2025)
The digital age offers businesses unique opportunities to build emotional connections with customers through social media. This study investigates the impact of social media activities on brand image and emotional attachment within the travel industry. Using a descriptive research design and causal-comparative approach, the research targets travel enthusiasts, social media users, tourists, influencers, and travel-related businesses. Data from 405 respondents were collected via a structured questionnaire and analyzed using SMART PLS, with descriptive statistics, correlation, regression analysis, and Cronbach’s alpha. The results reveal significant relationships among social media interactivity (SMI), social media benefits (SMB), social media rewards (SMR), brand image (BI), and emotional attachment (EA). SMB strongly influences BI, while BI is positively associated with EA, underscoring that a positive brand image enhances emotional bonds. Regression analysis confirms BI’s impact on EA. Social media interactivity and benefits foster deeper engagement, driving stronger emotional attachment and brand loyalty. These findings highlight the critical role of social media in shaping customer loyalty in the competitive travel industry.